The effect of comorbidity on the use of adjuvant chemotherapy and type of regimen for curatively resected stage III colon cancer patients. (15th January 2016) - Hsieh, Mei‐Chin; Thompson, Trevor; Wu, Xiao‐Cheng; Styles, Timothy; O'Flarity, Mary B.; Morris, Cyllene R.; Chen, Vivien W.
Abstract: Postsurgical chemotherapy is guideline‐recommended therapy for stage III colon cancer patients. Factors associated with patients not receiving adjuvant chemotherapy were identified in numerous studies; comorbidity was recognized as an important factor besides patient's age. We assessed the association between comorbidity and the use of adjuvant chemotherapy and type of chemotherapy regimen. Stage III colon cancer patients who underwent surgical resection were obtained from ten Centers for Disease Control and Prevention (CDC)‐NPCR Specialized Registries which participated in the Comparative Effectiveness Research (CER) project. Comorbidity was classified into no comorbidity recorded, Charlson, non‐Charlson comorbidities, number, and severity of Charlson comorbidity. Pearson chi‐square test and multivariable logistic regression were employed. Of 3180 resected stage III colon cancer patients, 64% received adjuvant chemotherapy. After adjusting for patient's demographic and tumor characteristics, there were no significant differences in receipt of chemotherapy between Charlson and non‐Charlson comorbidity. However, patients who had two or more Charlson comorbidities or had moderate to severe disease were significantly less likely to have chemotherapy (ORs 0.69 [95% CI, 0.51–0.92] and 0.62 [95% CI, 0.42–0.91], respectively) when compared with those with non‐Charlson comorbidity. In addition, those with moderate or severe comorbidities were more likely to receive single chemotherapy agent ( P  < 0.0001). Capecitabine and FOLFOX were the most common single‐ and multi‐agent regimens regardless of type of comorbidity grouping. Both the number and severity of comorbidity were significantly associated with receipt of guideline‐recommended chemotherapy and type of agent in stage III resected colon cancer patients. Better personalized care based on individual patient's condition ought to be recognized. Abstract : The authors show that both the number and severity of comorbidity are significantly associated with receipt of guideline‐recommended chemotherapy and type of chemotherapy agent in stage III resected colon cancer patients.